Multi-objective topology optimization of aero-engine accessory gearbox case based on compromise programming method - Huang, Hao; Wang, Zeng; Yang, Ziyi; Liu, Huaiju; Lu, Zehua (Science China. Technological sciences, 2025)
The accessory gearbox is a crucial component of the power transmission system of an aero-engine. The current design of the accessory gearbox case heavily relies on engineering experience, resulting in a bulky and heavy structure. This makes it increasingly challenging to meet the design requirements of high-power density. This work proposes a multi-objective topology optimization method based on the compromise programming method for the aero-engine accessory gearbox case. By locally thinning the gearbox case wall thickness, the case weight is reduced by 12.7%, and the maximum Mises stress is also reduced by 19.7% compared to the initial design scheme. Furthermore, the maximum vibration acceleration amplitude is reduced by 23.9%. These results provide a new solution for the lightweight design of the aero-engine accessory gearbox case.